Managing Sudden Stops - Eichengreen, Barry; Gupta, Poonam (World Bank, Washington, DC, 2016)
The recent reversal of capital flows to emerging markets has pointed up the continuing relevance of the sudden stop problem. This paper analyzes the sudden stops in capital flows to emerging markets since 1991. It shows that the frequency and duration of sudden stops have remained largely unchanged, but that the relative importance of different factors in their incidence has changed. In particular, global factors appear to have become more important relative to country-specific characteristics and policies. Sudden stops now tend to affect different parts of the world simultaneously rather than bunching regionally. Stronger macroeconomic and financial frameworks have allowed policy makers to respond more flexibly, but these more flexible responses have not guaranteed insulation or mitigated the impact of the phenomenon. These findings suggest that the challenge of understanding and coping with capital-flow volatility is far from fully met.